2019
DOI: 10.1177/1178636119889629
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AcrAB-TolC Efflux Pump Genes and Detection of Mutation in Efflux Repressor AcrR from Omeprazole Responsive Multidrug-Resistant Escherichia coli Isolates Causing Urinary Tract Infections

Abstract: Antimicrobial resistance poses a threat in the treatment of infectious diseases in Bangladesh as well as in the world. Multidrug-resistant (MDR) Enterobacteriaceae, the most common cause of one such infectious disease, urinary tract infection (UTI), has contributed to the escalating problem of selecting empiric antibiotics against UTIs. The aim of this study was to investigate the presence of the efflux pump in MDR Escherichia coli isolates from UTI in the North-East region of Bangladesh, to isolate and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The best-described RND pump is AcrAB-TolC, found in Salmonella enterica serovar Typhimurium and Escherichia coli . As efflux pumps underpin antibiotic resistance in essentially all bacteria of clinical and veterinary importance ( 12 , 13 ), there is ongoing active research into the development of efflux inhibitors to potentiate the action of existing antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The best-described RND pump is AcrAB-TolC, found in Salmonella enterica serovar Typhimurium and Escherichia coli . As efflux pumps underpin antibiotic resistance in essentially all bacteria of clinical and veterinary importance ( 12 , 13 ), there is ongoing active research into the development of efflux inhibitors to potentiate the action of existing antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the distribution of efflux pumps genes among ESBL producing Enterobacterales isolates were found to be oqxB (67.63%), oqxA (62.59%) and qepA (3.6%), respectively. However, this efflux pump mediated drug resistance mechanism of bacteria can be subdued using various efflux inhibitory molecules [ 24 ], for instance, the susceptibility of antibiotics against multidrug-resistant bacteria (that developed exclusively due to efflux pump mechanisms) can be enhanced in presence of efflux pump inhibitor such as omeprazole [ 25 ]. Further, the genome sequencing analysis of multidrug-resistant strains that might reveal the potential genes that are associated with multidrug efflux pumps and once the genes and gene products are identified, the molecular docking studies that may further help in developing appropriate efflux pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Chowdhury et al 30 found that Overexpression of the AcrAB-TolC efflux pump is an intrinsic mechanism of multidrug resistance in Gram-negative bacteria, It can be due to the mutation in AcrR gene which is the repressor of the AcrAB operon system.…”
Section: Discussionmentioning
confidence: 99%